MORPHOLOGICAL CREATIVITY AND NEOLOGISMS IN SOCIAL MEDIA ENGLISH - Anna Schneider (International Journal of Literature and Language Studies, 2026)
This article investigates morphological creativity and neologisms in social media English within the broader field of linguistics and applied language studies. The study uses 1,500 public posts and comments collected from open social media discussions on entertainment and technology and applies morphological classification of blends, compounds, affixation, clipping, acronyms, and playful respellings. The main finding is that blending, compounding, and clipping were the most productive strategies because they allowed users to compress stance and humour into short forms. The article argues that social media English provides rich evidence for rapid lexical innovation and participatory word formation. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.